Pre-post evaluation of a training activity on food and physical activity addressed to university students of the Melilla campus - Fernández -Gómez, E.; Sánchez-Ojeda, MA.; Enrique-Mirón, C. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2019)
Chronic non-communicable diseases are produced by an unhealthy lifestyle, like a poor diet and not perform physical activity. The knowledge about the diet and the physical exercise of the university students of the sanitary and educative field is essential for the promotion of the health and the prevention of illnesses. The objective of the study was to know how an extracurricular training activity influences the students in the knowledge about the nutrition and the physical activity. Through a pre-post design the answers given to an ad hoc questionnaire are analyzed. The results show the increase in knowledge after the educational intervention, with nursing students achieving the best scores. The extracurricular training activities are an effective instrument to acquire and reinforce, in a positive and highly motivational way, the knowledge of university students thus allowing their work in the field of health education.